From Political Rhetoric to Concrete Actions – A Human Rights-Based Approach to the Sustainable Development Goals in Africa - Ashukem, Jean-Claude N.; Odaghara, Chidinma Therese; Kabaseke, Charlotte; Kabata, Faith (African Journal of International and Comparative Law, 2025)
This article examines the relevance and application of a Human Rights-Based Approach (HRBA) in achieving the Sustainable Development Goals (SDGs) in Africa. The authors argue that the HRBA anchored on the principles of equality and non-discrimination, participation and inclusion, and accountability and rule of law offers a transformative framework for operationalising development in line with human rights standards. Drawing on the 2003 United Nations Human Rights-Based Approach to Development Cooperation framework, the paper explores how African states can adapt HRBA mechanisms to local governance realities to empower marginalised populations and strengthen state accountability. It further analyses the relationship between human rights and the SDGs, proposing HRBA as a pragmatic avenue for integrating human rights norms into sustainable development processes. Through a discussion of both the advantages and challenges of HRBA implementation, the authors conclude that aligning the SDGs with human rights obligations can foster inclusive, equitable, and accountable development outcomes across the continent.